2019
DOI: 10.1097/rnj.0000000000000098
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Short-term Mindfulness-Based Intervention on Comfort of Stroke Survivors Undergoing Inpatient Rehabilitation

Abstract: Purpose The aim of the study was to evaluate the effectiveness of a modified short-term mindfulness-based intervention on improving the mindfulness, comfort, and ambulation ability of stroke survivors undergoing inpatient rehabilitation in Wuhan, China. Design A two-group, nonrandomized, nonconcurrent design was used. Method Participants undergoing inpatient rehabilitation were nonrandomly divided into contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…Actual session length varied from 1.75 to 2.5 h duration. In one of the few inpatient studies, Wang et al (2019a) taught mindfulness in a stroke rehabilitation setting in two, weekly 90-min group sessions with individual daily practice for 2 weeks.…”
mentioning
confidence: 99%
“…Actual session length varied from 1.75 to 2.5 h duration. In one of the few inpatient studies, Wang et al (2019a) taught mindfulness in a stroke rehabilitation setting in two, weekly 90-min group sessions with individual daily practice for 2 weeks.…”
mentioning
confidence: 99%
“…A psychotherapy incorporating psychoeducation, behavioral activation, and adherence enhancement strategies, in collaboration with caregivers and providers, improves depression symptoms in poststroke depression (Alexopoulos et al, 2012). Mindfulness-based interventions improve physical comfort and quality of life and reduce anxiety, depression, and fatigue in stroke survivors undergoing rehabilitation (Lawrence et al, 2013;Ulrichsen et al, 2016;Wang et al, 2019Wang et al, , 2020Wrapson et al, 2021). Thus, we chose to implement focused skill-building interventions incorporating psychoeducation, mindfulness, and behavioral activation while incorporating the interdisciplinary medical team and caregivers as much as possible (Jaywant et al, 2021).…”
Section: Public Significance Statementmentioning
confidence: 99%
“…A meta-analysis of two studies with a control group (N = 184 participants), including one RCT and one nonrandomized control group pretest-posttest design study, found no statistically significant effect of MABIs on mindfulness compared to control groups (SMD = 0.87, 95% CI = [−0.60, 2.34]; see Figure 5). The included studies measured the effects of MABIs on mindfulness compared to either a treatment as usual control group (M. Wang et al, 2019) or an attention control group providing stress management education (X. Wang et al, 2020).…”
Section: Effects Of Mabis On Quality Of Life and Mindfulnessmentioning
confidence: 99%
“…Wang et al, 2020). MABIs in the included studies were 2 weekly mindfulness training sessions (1.5-hr group practice with guided individual daily practice for 20 min) by M. Wang et al (2019); and 8 weekly group-based MBCT sessions (2 hrs/session) by X. Wang et al (2020).…”
Section: Effects Of Mabis On Quality Of Life and Mindfulnessmentioning
confidence: 99%